If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1t = 3(t + 1) + -5 Reorder the terms: 4 + -1t = 3(1 + t) + -5 4 + -1t = (1 * 3 + t * 3) + -5 4 + -1t = (3 + 3t) + -5 Reorder the terms: 4 + -1t = 3 + -5 + 3t Combine like terms: 3 + -5 = -2 4 + -1t = -2 + 3t Solving 4 + -1t = -2 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 4 + -1t + -3t = -2 + 3t + -3t Combine like terms: -1t + -3t = -4t 4 + -4t = -2 + 3t + -3t Combine like terms: 3t + -3t = 0 4 + -4t = -2 + 0 4 + -4t = -2 Add '-4' to each side of the equation. 4 + -4 + -4t = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -4t = -2 + -4 -4t = -2 + -4 Combine like terms: -2 + -4 = -6 -4t = -6 Divide each side by '-4'. t = 1.5 Simplifying t = 1.5
| 37+2x=117 | | -2(t-3)+7t=9t-2 | | -x^3+2x^2=5x^2-20x+20 | | 7(6a-1)=6(7a+1) | | 8q-7=33 | | 50+1.5b=75+1b | | 96=12+n | | (x*7.81)+x=3800000 | | x^3+3x^2-20x+20=0 | | 3(3x-6)-4=9x-22 | | 34-3y=25 | | 6x^2-7x-100=0 | | 3(a-2)=36 | | 3z^2+4z=8z-5 | | 56-3c=4c | | p^2+8p+9= | | V^2-10v+22=8-v | | 2(3n-4)=(3n+6)+9 | | 17.4x^2+71.34x+25.752= | | 16m+5n-6m+10n= | | 8x-5y-x-9-y= | | 5v^2-13v-4=2 | | 5a+3+8a-9=72 | | 7(4x+7)+5=28x+54 | | 600-423= | | 5b=36+4b | | -9+3(3n-8)=-105 | | -8(x+4)+3=29 | | -2(n+4)=6n+10+n | | r^2+2r-5=-2 | | 2r-7=6r-27 | | -14-{-421}= |